Minimal Stabilization Time for Ultra-short Heart Rate Variability Measurements in Professional Soccer - Forner-Llacer, Francisco; Aranda-Malaves, Rodrigo; Aranda Malavés, Rafael; Calleja-Gonzalez, Julio; Perez-Turpin, Jose Antonio; Gonzalez-Rodenas, Joaquin (International Journal of Sports Medicine, 2020)
The main aims of this study were: 1) to compare 1-minute RMSSD measurements using different stabilization times between them and also with the criterion; and 2) to determine the agreement between every 1-minute RMSSD measurement with the criterion in professional soccer players. Seven hundred eighteen HRV measurements from professional soccer players were taken. HRV was calculated from 5 to 10 minutes (criterion) and from 1-minute windows with different pre-stabilization times. Friedman and post-hoc tests were applied to compare 1-minute and criterion measurements. Effect size was considered to describe magnitude of change. To determine agreement, Spearman’s correlation was applied, and Bland–Altman analysis was also done between each ultra-short HRV time window and the 5-minute HRV criterion period. The 1-minute HRV without any pre-stabilization time was the only one different from all the other 1-minute measurements that included 1 or more minutes of pre-stabilization (p<0.001). One-minute HRV measurements with 1 or more minutes of pre-stabilisation were highly correlated with those for the criterion period. One-minute HRV without pre-stabilization showed the lowest correlation and the highest bias from the criterion. It is concluded that 1-minute HRV measurements with a prior 1-minute or longer pre-stabilization time are valid to measure HRV in professional male soccer players.
Keywords: training status; fatigue-recovery process; HRV; professional soccer